P145 Evaluation and quantification of treatment preferences for patients with asthma or copd using discrete choice experiment surveys. (15th November 2016) - Svedsater, H; Hilton, E; Leather, D; Robinson, T; Bradshaw, L; Doll, H; Nafees, B
Abstract : Background: The impact of asthma and chronic obstructive pulmonary disease (COPD) on patients' lives can be substantial, despite the use of maintenance medication. To understand the treatment preferences of patients with asthma or COPD, a discrete choice experiment (DCE) survey was developed, based on factors identified in a previous stage of this study as being influential. 1 Methods: UK residents aged ≥18 years currently receiving treatment for asthma or COPD were recruited by a commercial recruitment panel (Global Perspectives) to take part in an internet-based survey. Participants provided demographic information and ranked eight attributes of treatment using an 8-point Likert scale (0 = extremely important–8 = not at all important). Furthermore, treatment preferences were elicited by a DCE survey; participants chose between two hypothetical treatments that differed in terms of previously identified influential attributes. 1 A mixed logit regression model assessed DCE preferences for each condition separately. Results: Data were collected from 302 participants, who generally had poorly controlled asthma (indicated by Asthma Control Test™ scores ≤19/25) or experienced a high impact of COPD (indicated by COPD Assessment Test™ scores >20/40) and had been living with asthma or COPD for approximately 23.4/8.5 years (Table). Most attributes of participants' current treatment were similar for the asthma and COPD populations; participants ranked having well-controlled symptoms all day as most important while the monthly cost was ranked as least important (Table). Treatment preferences from most to least important (with some degree of variation between conditions) were: reduced sleep disturbance, inexpensive, easy/convenient to use, reduced flare ups/exacerbations, enabled participation in all desired physical activities, controlled symptoms all day, enabled participation in all desired social activities and reduced medication frequency (Table); all attributes were significant in influencing treatment choices. Conclusions: All identified valued attributes of medications had a significant impact in the DCE, despite differences in relative importance, and should be considered by healthcare professionals when discussing maintenance treatment options with patients with asthma and COPD. These factors should be considered in the development of future medications. Reference: Svedsater, et al . AJRCCM 2016;A1747.